The expanded spectrum of neuromyelitis optica: evidences for a new definition - Marco A Lana-Peixoto; Dagoberto Callegaro (Arquivos de Neuro-Psiquiatria)
Neuromyelitis optica (NMO) has been traditionally described as the association of recurrent or bilateral optic neuritis and longitudinally extensive transverse myelitis (LETM). Identification of aquaporin-4 antibody (AQP4-IgG) has deeply changed the concept of NMO. A spectrum of NMO disorders (NMOSD) has been formulated comprising conditions which include both AQP4-IgG seropositivity and one of the index events of the disease (recurrent or bilateral optic neuritis and LETM). Most NMO patients harbor asymptomatic brain MRI lesions, some of them considered as typical of NMO. Some patients with aquaporin-4 autoimmunity present brainstem, hypothalamic or encephalopathy symptoms either preceding an index event or occurring isolatedly with no evidence of optic nerve or spinal involvement. On the opposite way, other patients have optic neuritis or LETM in association with typical lesions of NMO on brain MRI and yet are AQP4-IgG seronegative. An expanded spectrum of NMO disorders is proposed to include these cases.